2007
DOI: 10.1016/j.juro.2007.05.170
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Tubularized Incised Plate Versus Onlay Island Flap Urethroplasty for Penoscrotal Hypospadias

Abstract: In this series the overall complication rate was similar for tubularized incised plate and onlay urethroplasty. Despite similar urethroplasty calibers, the uroflow curves and fistula positions in patients undergoing tubularized incised plate repair suggest that the neourethra distal to the fistula may be relatively narrow, creating flow resistance and leading to proximal fistula. Longer followup and close monitoring are needed before embracing one approach over the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 20 publications
3
69
0
6
Order By: Relevance
“…In agreement with the findings of Braga et al, there was no statistically significant difference in the complication rate in relation to the performed technique [27]. However, a significantly higher complication rate was encountered in patients with scrotal (23.3%) and perineal (100%) hypospadias and in patients requiring scrotoplasty (26.1% versus 12.1% in patients with normal scrotum).…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with the findings of Braga et al, there was no statistically significant difference in the complication rate in relation to the performed technique [27]. However, a significantly higher complication rate was encountered in patients with scrotal (23.3%) and perineal (100%) hypospadias and in patients requiring scrotoplasty (26.1% versus 12.1% in patients with normal scrotum).…”
Section: Discussionsupporting
confidence: 90%
“…The proportion of patients who experience complications after undergoing hypospadias repair as an infant is reportedly 2-15% [1,[11][12][13][14][15]. However, this rate varies depending on the degree of hypospadias and the surgical technique used.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded there is a spontaneous normalization of the urinary flow in boys after TIP repair, but the need for long-term follow up beyond puberty is required. 22 Braga et al 23 performed comparative analysis between two groups of patients with penoscrotal hypospadias who underwent either tubularized incised plate or transverse island flap onlay urethroplasty and reached the same conclusion. They retrospectively reviewed 75 consecutive patients with penoscrotal hypospadias.…”
Section: Voiding Difficulties Following Hypospadias Repairmentioning
confidence: 92%